Model skończenie stanowy niemieckich wyrazów pojedynczo i wielokrotnie złożonych - Junczys-Dowmunt, Marcin (Investigationes Linguisticae, 2007)
This paper summarizes the results of my Master's thesis and the main points of a talk I presented at the seminar of the Department of Applied Logic at the Adam Mickiewicz University in Poznań.It gives a short overview of the structure of German compounds and newer research concerning the role of the so-called interfixes. After an introduction to the concept of finite-state transducers the construction of a transducer used for naive compound segmentation is described. Tag-based finite-state methods for the further analysis of the found segments are given and discussed. Distributional transducer rules, for the construction of which I assume the existence of local and global morphological contexts, are proposed as means of disambiguation of the analyzed naive segmentation results.